Capitation Management Through Performance-Based Capitation Mechanism of Primary Health Care in Malang, Indonesia - Purnamasari, Ayu Tyas; Ningrum, Herlinda Dwi; Ardhiasti, Anggi; Zahroh, Asri Hikmatuz (Kesmas, 2024)
Primary health care (PHC) has one of the largest funding sources, capitation, which BPJS Healthcare Security transfers monthly. Capitation fund receipts were frequently insufficient due to failure to meet performance-based capitation/Kapitasi Berbasis Kinerja (KBK) targets, including for PHC in Malang City, Indonesia. This study aimed to examine the management and utilization of capitation funds through a KBK mechanism. This descriptive study used a qualitative approach supported by quantitative data. This study was conducted from July to August 2023 and purposely selected nine informants from BPJS Healthcare Security, the local health office, and PHC. The interviews were transcribed verbatim and analyzed using a thematic analysis approach. Three themes were identified from data analysis: revenue allocation, utilization allocation, and budget expenditure appropriateness. The use of capitation follows the Mayor's regulations, which allocate service and operational costs. However, remaining capitation funds always occur due to unavoidable conditions. Separating accounts between capitation and other funding sources is necessary to track capitation utilization. Therefore, BPJS Healthcare Security needs to participate in capitation reporting and monitoring.